Acrylate formation from CO2 and ethylene: catalysis with palladium and mechanistic insight1. Issue 54 (11th July 2015) - Stieber, S. Chantal E.; Huguet, Núria; Kageyama, Takeharu; Jevtovikj, Ivana; Ariyananda, Piyal; Gordillo, Alvaro; Schunk, Stephan A.; Rominger, Frank; Hofmann, Peter; Limbach, Michael
<x xml:space="preserve">Abstract</x> The first palladium catalyst for the reaction of CO2, alkenes and a base to acrylates is reported (TON up to 50).